2016
DOI: 10.1021/jacs.6b04636
|View full text |Cite
|
Sign up to set email alerts
|

Computation Sheds Insight into Iron Porphyrin Carbenes’ Electronic Structure, Formation, and N–H Insertion Reactivity

Abstract: Iron porphyrin carbenes constitute a new frontier of species with considerable synthetic potential. Exquisitely engineered myoglobin and cytochrome P450 enzymes can generate these complexes and facilitate the transformations they mediate. The current work harnesses density functional theoretical methods to provide insight into the electronic structure, formation, and N-H insertion reactivity of an iron porphyrin carbene, [Fe(Por)(SCH3)(CHCO2Et)](-), a model of a complex believed to exist in an experimentally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
131
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(149 citation statements)
references
References 127 publications
(481 reference statements)
17
131
1
Order By: Relevance
“…Similar “nitrene radical” intermediates have recently been spectroscopically characterized for cobalt porphyrins and other systems. 2628 Formation of the saturated N-heterocycle proceeds via either H atom abstraction followed by radical rebound or direct insertion of the nitrene moiety into the benzylic C–H bond and then forms a pyrrolidine complex. Finally, reaction with Boc 2 O releases the Boc-protected N-heterocycle and regenerates the catalyst (see the Supporting Information for hypothetical scheme based on 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar “nitrene radical” intermediates have recently been spectroscopically characterized for cobalt porphyrins and other systems. 2628 Formation of the saturated N-heterocycle proceeds via either H atom abstraction followed by radical rebound or direct insertion of the nitrene moiety into the benzylic C–H bond and then forms a pyrrolidine complex. Finally, reaction with Boc 2 O releases the Boc-protected N-heterocycle and regenerates the catalyst (see the Supporting Information for hypothetical scheme based on 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using model systems, recent DFT studies have investigated the nature of the putative iron carbenoid intermediate, shedding light on factors governing its formation and reactivity [5052]. In particular, work by Sharon et al .…”
Section: Outlook - Future Opportunities For Hemoprotein Engineeringmentioning
confidence: 99%
“…In particular, work by Sharon et al . on carbene N–H insertion [52] indicated that altering the basicity of the enzyme active site may allow access to aliphatic amines, potentially extending the substrate scope from the aromatic amines reported to date [9,17]. This proposal has not yet been tested experimentally.…”
Section: Outlook - Future Opportunities For Hemoprotein Engineeringmentioning
confidence: 99%
“…Specifically, carbene‐based organometallic catalysts have been synthesized and characterized . These catalysts have also been found to promote C−H bond activation, epoxidation, and N−H insertion . In this context, efforts have been made to fine‐tune the equatorial ligands, most notably the synthesis and reactivity studies of an iron(IV)‐oxo complex bearing a macrocyclic tetracarbene ligand ([(L NHC )Fe IV (O)(CH 3 CN)] 2+ ( 1 ) where L NHC =3,9,14,20‐tetraaza‐1,6,12,17‐tetraazoniapenta‐cyclohexacosane‐1(23),4,6(26),10,12(25),15,17(24),21‐octaene) .…”
Section: Introductionmentioning
confidence: 98%